Arbuscular Mycorrhizal Fungi Colonization of Jatropha curcas Roots and Its Impact on Growth and Survival under Greenhouse-Induced Hydric Stress - Solís Ramos, Laura Yesenia (2023)
Abstract: Arbuscular mycorrhizal fungi (AMF) provide benefits to host plants by enhancing nu-trition and overall fitness. In this study, AMF species were isolated from the soil rhizosphere of Jatropha curcas and were identified and evaluated for their potential in fostering the development of Jatropha seedlings within a controlled greenhouse environment. The first experiment assessed the interplay between hydric stress and AMF inoculation on mycorrhizal colonization. The next ex-periment examined the impact of quercetin on mycorrhizal colonization. Out of 204 glomero-spores corresponding to 28 species spanning 10 genera, Acaulospora (14) and Scutellospora (5) were the most abundant taxa. Strikingly, nine species are new records for Costa Rica. Mycorrhizal colonization was observed in 43.2% of Jatropha plants (34.7% by AMF typical hyphae; arbuscules 8.9%; coils 5.6% and vesicles 5.4%). Significant survival effects due to AMF inoculation under hydric stress were observed. On day 85, non-mycorrhizal plants subjected to hydric stress showed a mere 30% survival rate, whereas their mycorrhizal counterparts under hydric stress exhibited survival rates of 80% and 100% with and without irrigation, respectively. Furthermore, plants with irri-gation and mycorrhizas showed greater hydric stress tolerance and superior growth. The inocu-lated plants, irrespective of irrigation, demonstrated mycorrhizal colonization rates of 63% and 72%, respectively. Quercetin did not affect Jatropha's growth, but there were differences in AMF root colonization. In summary, these findings accentuate the viability of a native consortium in augmenting Jatropha survival, warranting consideration as a potent biofertilizer within green-house settings. The AMF described can be used for Jatropha propagation programs.